Lessons from The Gulf : Female Indigenous Emirati Students' Persistence and Success at University. - McClusky, Beverley; Allen, Bill (Student Success v.14 n.1 p.9-20 https://doi.org/10.5204/ssj.2292, 2023)
Students' persistence and success remain significant issues for universities worldwide, but Tinto (2017a; 2017b) argued that universities need to listen to perspectives of students themselves in identifying what causes them to persist and succeed. This article reports on such perspectives of Indigenous Emirati, Muslim women at one public university in the United Arab Emirates (UAE). Data collection from original doctoral research involved an initial, customised survey completed by 22 Emirati women with subsequent interviews conducted with a further 21 female students. Data for the purpose of this article were analysed using thematic analysis. Findings are presented within Tinto's framework: goals; sense of belonging; self-efficacy; responses to curriculum; and their impact on students' motivation. Tinto's framework provides a valuable insight in understanding the women’s experiences, and their statements around persistence and success have important implications for understanding women’s progression in higher education in a society where male authority remains significant. [Author abstract]